Fenomenologiczne wątki filozofii dramatu - Wesołowska, Agnieszka (Folia Philosophica, 2018)
The paper depicts phenomenological threads of philosophy of drama. My aim here is to analyse the dramatic creature in its phenomenological aspect rooted in the thought of Józef Tischner. In analysis of axiological-agatological character of the egotic sphere, Tischner shows ego as a creature of internal rift. In the paper I focus on three threads of Tischner’s philosophy of drama and his concept of dramatic creature. First, the issue of the source experience as a starting point of philosophy. Second, the egotic thread; and thirdly, the dramatic-one, that is axiological interpretation of egology. Taking into account some selected issues which are core of Tischner’s philosophy of drama, makes it able to show his thought in his phenomenological provenance.